2003
DOI: 10.1029/2003gl018153
|View full text |Cite
|
Sign up to set email alerts
|

Small, highly reflective ice crystals in low‐latitude cirrus

Abstract: [1] At low latitudes, cirrus are ubiquitous and can be in excess of 100°C colder than the surface, limiting the amount of sunlight absorbed by the earth's atmosphere and surface, and reducing its loss of heat. Here we present aircraft measurements within cirrus over southern Florida indicating that ice crystals have smaller sizes and are more reflective than is assumed in most current climate models. If the measurements are generally representative of low-latitude cirrus, they point to a first-order correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 31 publications
9
92
4
Order By: Relevance
“…These small ice crystal effective dimensions have been chosen so as to maximise scattering so that differences between ice crystal shapes may become more apparent. However, such a small D e value might occur in tropical cirrus (Garrett et al 2003). The difference in D e between the two shapes is 1.18 µm and such a small difference will not affect the conclusions of this paper.…”
Section: Impact Of Ice Crystal Geometrymentioning
confidence: 78%
“…These small ice crystal effective dimensions have been chosen so as to maximise scattering so that differences between ice crystal shapes may become more apparent. However, such a small D e value might occur in tropical cirrus (Garrett et al 2003). The difference in D e between the two shapes is 1.18 µm and such a small difference will not affect the conclusions of this paper.…”
Section: Impact Of Ice Crystal Geometrymentioning
confidence: 78%
“…The observation of a decreasing effective radius with altitude is in agreement with observations and model calculations in the tropics presented by Chen et al (1997), who show a decreasing effective radius with altitude. Also Garrett et al (2003) observed a decreasing effective radius with decreasing ambient temperature in the sub-tropics. They suggest that this is caused by the fact that homogeneous ice nucleation favours smaller ice crystals at colder temperatures, due to the exponential dependence of the saturation vapour pressure over ice on temperature (Kärcher and Lohmann, 2002), rather than the effect of ageing of the cirrus cloud or gravitational settling.…”
Section: Effective Radius and Ice Water Contentmentioning
confidence: 92%
“…Yet, if present, small ice crystals are important for the radiative properties of these clouds (Garrett et al, 2003). Two recent studies by Garrett (2010, 2011) used remote sensing observations by the MODIS satellite as an independent method to constrain the frequency of thin cirrus clouds composed of small ice particles with an effective radius below 20 µm.…”
Section: Introductionmentioning
confidence: 99%